Knowledge and attitude towards biomedical science career options among biomedical science undergraduate students in International Islamic University Malaysia - Mohamad Azmadi, Muhammad Alif Amirul; Kaderi, Mohd Arifin; Zainuddin, Norafiza (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2022)
Biomedical sciences are a group of sciences that use elements of natural science, formal science, or both to develop knowledge, interventions, or technology for use in healthcare or public health. Biomedical Science covers a wide range of fields of research that focuses on healthcare-relevant fields of biology and chemistry. The rate of biomedical science IIUM graduate employability in 2020 was 70.7% (GE, 2014). This cross-sectional study aimed to determine the level of knowledge and attitude towards biomedical science career options among Biomedical Science undergraduate students in IIUM Kuantan, and the association between the knowledge & attitude career option awareness. This study involved 89 respondents randomly chosen based on specific criteria. Data was collected through the distribution of questionnaires online and data was analyzed using Statistical Package for Social Sciences (SPSS) version 22. From this study, it can be summarized that the Biomedical Science undergraduate students in International Islamic University Malaysia (IIUM) Kuantan have a good level of knowledge and moderate attitude towards biomedical science career options. Significant relationships were found between knowledge and attitude towards career options among the respondents. Overall, it can be concluded that adequate attitude led to the good knowledge of the respondents, yet additional preparations for a great variety of careers from research and the sciences to entrepreneurship may boost the employability rate of the Biomedical Science graduates.